Assessing the Exposome with External Measures: Commentary on the State of the Science and Research Recommendations - Turner, Michelle C.; Nieuwenhuijsen, Mark; Anderson, Kim; Balshaw, David; Cui, Yuxia; Dunton, Genevieve; Hoppin, Jane A.; Koutrakis, Petros; Jerrett, Michael (Annual Review of Public Health, 2017)
The exposome comprises all environmental exposures that a person experiences from conception throughout the life course. Here we review the state of the science for assessing external exposures within the exposome. This article reviews (a) categories of exposures that can be assessed externally, (b) the current state of the science in external exposure assessment, (c) current tools available for external exposure assessment, and (d) priority research needs. We describe major scientific and technological advances that inform external assessment of the exposome, including geographic information systems; remote sensing; global positioning system and geolocation technologies; portable and personal sensing, including smartphone-based sensors and assessments; and self-reported questionnaire assessments, which increasingly rely on Internet-based platforms. We also discuss priority research needs related to methodological and technological improvement, data analysis and interpretation, data sharing, and other practical considerations, including improved assessment of exposure variability as well as exposure in multiple, critical life stages.
Keywords: global positioning systems